Muslim politics in Malaysia and the democratization process - Lukman Thaib, (Universiti Kebangsaan Malaysia, 2013)
This article will address the Muslim politics in Malaysia in the light of the broader shifts towards democratization and Islamization by focusing on politics among the majority ethnic Malay community, followed an overview of the ideological rivalry between UMNO and PAS, with special reference to the electoral performances of these parties in the past three general elections (November 1999, March 2004 and March 2008) . It then explores the underlying reason for the perceived importance of Islam in understanding the voting trend among the Malay-Muslim electorate which raised the question to what extent was the discourse on Islam instrumental in persuading the Malays to switch their support from PAS to the UMNO during the 2004 elections, and in the process of continued participation as an ‘Islamic Party’ in Malaysian mainstream politics what factors were that encouraged the PAS leaders to compromises and to play by the ‘rule of democracy’. In the concluding part of the article the writer also provide with an overview on reform agenda of Civilizational Islam (Islam Hadhari) under premiership of Tun Abdullah Ahmad Badawi and the current Malaysia’s Transformation Programme (GTP) under the leadership of Dato’ Sri Mohd Najib Tun Abdul Razak.